An effective transmit packet coding with trust-based relay nodes in VANETs - Hammood, Omar A.; M. N. M., Kahar; Hammood, Waleed A.; Hasan, Raed Abdulkareem; Mohammed, Mostafa Abdulghfoor; Yoob, Ayoob A.; Sutikno, Tole (IAES, 2020)
ehicular ad-hoc networks (VANETs) are characterized by limited network resources such as limited bandwidth and battery capacity. Hence, it is necessary that unnecessary use of network resources (such as unnecessary packet transfers) is reduced in such networks so that the available power can be conserved for efficient multicast communications. In this paper, we have presented a Transmit Packet Coding (TPC) Network Coding in VANET to ensure reliable and efficient multicasting. With network coding, the number of transmitted packets over the network can be reduced, ensuring efficient utilization of network devices and resources. Here, the trust-based graph optimization is performed using Cuckoo search algorithm to select the secure relay nodes. The experimental results showed the superiority of the presented approach compared to the existing techniques in terms of throughput, latency, hop delay, packet delivery ratio, network decoder outage probability, and block error rate.